Effect of Tree Age on Water Requirement of Pomegranate under Localized Irrigation System - Bafkar, Ali; Karimi, Mosayeb; Rad, Mohammad Hadi (Annals of Arid Zone, 2020)
In this study, water requirements of pomegranate (adult and young plants), with regard to age and tree canopy, were estimated for a 2-year period for climatic conditions of Yazd province. The results showed that the amount of water use by young trees was less by about 6500 m3 in comparison to mature trees during the growth period, which was related to the canopy of trees. During the growing months, a large difference was observed in evapotranspiration. The maximum and minimum amount of water use was in July and November, respectively. In the design of localized irrigation systems, the maximum required discharge rate for pomegranate orchards in July was estimated to be 0.71 L s-1 ha-1 for mature trees and 0.27 L s-1 ha-1 for young trees. The obtained relationships showed that it is possible to accurately estimate the irrigation requirement of pomegranate trees with respect to their age. Key words: Pomegranate, pressurized irrigation, shadow surface, water requirement, Yazd province.